Extração de compostos fenólicos do resíduo de caju (Anacardium occidentale L.) visando aplicação cosmética - Alves, Fábia Rafaella Silva (2023)
Cashew apple bagasse (Anacardium occidentale L.) is an agroindustry by-product with a composition rich in cellulose, hemicellulose, and lignin. In addition, cashew apple bagasse (CAB) is an important source of phenolic compounds, which opens up possibilities for the generation of value-added products. In this context, the present work aimed to obtain an extract rich in phenolic compounds from CAB, using enzyme-assisted extraction as a sustainable method, for cosmetic application. The CAB was subjected to liquid hot water (LHW) and steam explosion (SE) pre-treatments, and characterized by FTIR, DRX, and lignocellulosic composition. Then, enzyme-assisted extraction (EAE) of pre-treated CAB was evaluated using a cellulolytic cocktail. The effects of enzyme load, solids load, and incubation time were investigated and optimized using a rotational central composite design (RCCD) 23. The extracts obtained were evaluated for their phenolic composition, in vitro antioxidant activity, cellular antioxidant activity, sugar content, and cytotoxicity. The results showed that the pre-treatments modified the structure of the residue, removing amorphous fractions, and making the material more accessible to enzymes. In addition, the pre-treatment by LHW associated with the enzymatic cocktail favored the greater release of phenolics from the lignocellulosic biomass (75,13 ± 3,5 mg GAE/L) and higher antioxidant activities, corresponding to 72.81% for the kidnapping of the radical DPPH and 241.04 ± 1.7 µM EQ Trolox/L for the kidnapping of the radical ABTS. The experimental design demonstrated that a longer incubation time (80 h) and solid load (8% and 10%, w/v) contributed to the increase in the content of phenolic compounds, obtaining, in the best condition, a phenolic concentration of 150.38 ± 10.0 mg GAE/L. Additionally, CAB extract showed antioxidant activity, evaluated by different mechanisms, with iron chelation ability, DPPH and ABTS radical scavenging presenting linear correlation with the concentration of solids. The extracts also showed cellular antioxidant activity, corresponding 36.03% of inhibition of Reactive Oxygen Species (ROS) for the extract obtained with 8% solids. These results are important indicators of a possible anti-aging application, opening perspectives for future formulations. Furthermore, the extract proved to be non-toxic, with cell viability greater than 95% in the MRC-5 fibroblast cell line. Therefore, enzymeassisted extraction of phenolic compounds from CAB proved to be viable and practicable. From a marketing point of view, this research contributes to the development of more efficient products and processes, environmentally sustainable, and optimizes the use of resources to obtain bioactive substances for the development of new cosmetic products.